Growth, Survival, and Body Composition of Transgenic Common Carp Cyprinus carpio 3rd Generation Expressing Tilapia Growth Hormone cDNA - . Kurdianto; . Alimuddin; Nurly Faridah; Goro Yoshizaki; Sri Nuryati; Mia Setiawati (HAYATI Journal of Biosciences, 2016)
Transgenic has been known as one of the applicable methods to improve growth performance of cultured fish. This study was performed to evaluate the growth performance, survival, and body composition of the 3rd generation of growth hormone (GH) transgenic common carp (TG). Juveniles (BW: 1.53 ± 0.03 g) were reared for 60 days in 250-L glass aquarium with stocking density of 25 fishes/aquarium. Fishes were fed with commercial feed (protein content 36%), three times a day to satiation. Growth and survival were measured every 20 days. Our results showed that TG fish has 1.49 times higher in average weight growth (p < 0.05) compared with the non-transgenic common carp (NT). Higher total feed consumption, survival, body protein content, protein and lipid retention, hepatosomatic index, and lower feed conversion ratio were also shown on TG fish compared with NT fish (p < 0.05). However, body lipid content and blood glucose level of TG fish were lower (p < 0.05) compared with the NT fish. Total ammonium nitrogen level in rearing media of TG fish was 51.78% lower (p < 0.05) than that of the NT fish. In conclusion, culturing of GH-TG common carp showed potential to achieve high productivity, efficient, and environmental-friendly aquaculture.